Adult height and diabetes control: is there an association?. Issue 3 (2nd September 2021) - Chetty, RR; Pillay, S
Abstract : Background: Obesity is commonly associated with diabetes mellitus (DM). The most frequent anthropometric index utilised to assess obesity is the body mass index (BMI), which uses height and weight as variables, but eliminates height as an independent analytical variable. Currently there are no data available on the relationship between adult height and glycaemic control in patients living with diabetes (PLWD) within the context of HIV infection. Objectives: This study aimed to determine an association between final adult height and glycaemic control in an HIV endemic area. Methods: Standardised clinic sheets were used from the DM clinic at Edendale Hospital, Pietermaritzburg, South Africa, from January 1, 2019 to December 31, 2019. Statistical analysis was done. Results: This study had 957 PLWD. In the height categories of < 1.40 m, 1.40–1.49 m, 1.50–1.59 m, 1.60–1.69 m, 1.70–1.79 m, 1.80–1.89 m and ≥ 1.90 m, there were 11, 60, 321, 343, 121, 26 and 2 patients respectively (with 73 patients having no height recorded). Taller patients had smaller waist circumferences and had poorer glycaemic control. In the lowest vs. highest height (< 1.40 m vs ≥ 1.90 m) categories, the HbA1c values were 8.49% vs. 12.45%, respectively, p = 0.019. Height had a strong positive association with diastolic blood pressure (DBP) ( p = 0.001). Those PLWD in the 1.80–1.89 m height cohort had higher triglyceride levels and lower high-density lipoprotein (HDL) levels when compared with the other height categories. Shorter PLWD with uncontrolled glycaemic control had significantly elevated systolic blood pressure. Gender and HIV infection had a non-significant role on height categories in PLWD. Conclusion: Taller height categories had poorer glycaemic control. Increasing height was strongly associated with increasing DBP. A higher DBP and triglyceride level with lower HDL level places these PLWD in a higher cardiovascular risk category. Strong emphasis needs to be placed on the monitoring of lipids and blood pressure in PLWD, this more especially in taller patients.